Analysis of the complexity of various linked lists (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In the concept of data structure, lists play a major role in data distribution. "Java lists areinterfaces that can be extended to collection interfaces." Lists can be implemented in twoways: array lists and linked lists. The array list is a class that provides an array of extensiblelists of Abstract Data Types (ADTs). Linked lists provide different implementations of theADT. Different types of linked lists are supported in the data structure, including singlylinked lists, double linked lists and circular linked lists. This article deals with the analysis ofarrays and linked lists (ie, singly linked lists) by performing operations such as inserting,deleting, and searching, and provides results and distributes data according to timecomplexity. Determine which is more appropriate and effective. This study uses the C andPython programming languages to analyze comparative studies of the performancedifferences in the complexity of various linked lists (linear and circular, single and double).This paper also shows execution times in various programming languages. Linked list is acomplex data structure, especially Useful in system or application programming. Linked listsdynamically allocate memory; use it to allocate memory in some locations. The runtime issimilar to an array, so it is also called dynamic data Structure